Hadith #3561 - Sunan Abi Dawud - Abdul 'Aziz bin Rafi' عبد العزيز بن رفيع; al-Hasan bin Muhammad al-Za'farani الحسن بن محمد الصباح الزعفراني; Safwan bin Umayyah; Salmah bin Shbyb سلمة بن شبيب; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Umayya bin Safwan bin Umayyah أمية بن صفوان بن أمية الجمحي; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: The hand which takes is responsible till it pays. Then al-Hasan forgot and said: (If you give something on loan to a man), he is your depositor ; there is no compensation (for it) on him.
Grade: Da'if